TINGKAT SELF ESTEEM PADA ANAK JALANAN DI JAKARTA - Devras, Eri; Kriswanto, Joko Suyono; Hermansyah, Hermansyah (Jurnal Aspirasi, 2013)
One of the issues on children’s welfare with a growing national concern is an issue of self-esteem level of the street children. Widespread phenomenon of street children with a low self-esteem level in Jakarta turns out to be a complex issue. In dealing with such problem, the government should be responsive to the phenomenon in which the street-children are increasing, while efforts to improve street children’s self-esteem are still not optimal. This can be seen from their behaviors that tend to be negative such as their issues on violence, drug abuse, sexual abuse, prostitution, sexually transmitted diseases (STDs / HIV / AIDS) and other problems. Extra efforts from the government of Jakarta City are needed to improve street children’s self-esteem through mentoring, counseling, education, employment, and so forth.